Prebiotic galacto-oligosaccharides mitigate the adverse effects of iron fortification on the gut microbiome: a randomised controlled study in Kenyan infants. Issue 11 (3rd August 2017) - Paganini, Daniela; Uyoga, Mary A; Kortman, Guus A M; Cercamondi, Colin I; Moretti, Diego; Barth-Jaeggi, Tanja; Schwab, Clarissa; Boekhorst, Jos; Timmerman, Harro M; Lacroix, Christophe; Karanja, Simon; Zimmermann, Michael B
Abstract : Objective: Iron-containing micronutrient powders (MNPs) reduce anaemia in African infants, but the current high iron dose (12.5 mg/day) may decrease gut Bifidobacteriaceae and Lactobacillaceae, and increase enteropathogens, diarrhoea and respiratory tract infections (RTIs). We evaluated the efficacy and safety of a new MNP formula with prebiotic galacto-oligosaccharides (GOS) combined with a low dose (5 mg/day) of highly bioavailable iron. Design: In a 4-month, controlled, double-blind trial, we randomised Kenyan infants aged 6.5–9.5 months (n=155) to receive daily (1) a MNP without iron (control); (2) the identical MNP but with 5 mg iron (2.5 mg as sodium iron ethylenediaminetetraacetate and 2.5 mg as ferrous fumarate) (Fe group); or (3) the identical MNP as the Fe group but with 7.5 g GOS (FeGOS group). Results: Anaemia decreased by ≈50% in the Fe and FeGOS groups (p<0.001). Compared with the control or FeGOS group, in the Fe group there were (1) lower abundances of Bifidobacterium and Lactobacillus and higher abundances of Clostridiales (p<0.01); (2) higher abundances of virulence and toxin genes (VTGs) of pathogens (p<0.01); (3) higher plasma intestinal fatty acid-binding protein (a biomarker of enterocyte damage) (p<0.05); and (4) a higher incidence of treated RTIs (p<0.05). In contrast, there were no significant differences in these variables comparing the control and FeGOS groups, with the exception that the abundance of VTGs of all pathogens was significantly lower in the FeGOS group compared with the control and Fe groups (p<0.01). Conclusion: A MNP containing a low dose of highly bioavailable iron reduces anaemia, and the addition of GOS mitigates most of the adverse effects of iron on the gut microbiome and morbidity in African infants. Trial registration number: NCT02118402.